Socioecological correlates of perceived cooking skills among Spanish adolescents: the EHDLA study - Hermosa-Bosano, Carlos; López-Gil, José Francisco (Frontiers in Public Health, 2025)
BackgroundIndividuals' perceptions of their cooking skills have been associated with healthier eating patterns. This study examines the socioecological factors associated with adolescents' cooking skills perceptions within a Spanish context. Key factors analyzed included sex, age, immigrant status, socioeconomic status, parental education, family structure, household size, schooling type, and area of residence.MethodsThis research used data from adolescents aged 12–17 who took part of the Eating Healthy and Daily Life Activities (EHDLA) study (Region of Murcia, Spain). A chi-squared test and generalized linear models with binomial distribution were used to examine associations.ResultsPerceptions of cooking skills varied among adolescents; 16.3% rated their cooking skills as very adequate. Perceived cooking skills were significantly associated with sex, socioeconomic status (SES), and type of schooling. Female adolescents had over twice the odds of perceiving their cooking skills as very adequate compared to males [odds ratio (OR) = 2.05, 95% confidence interval (CI): 1.40–3.03, p < 0.001]. Adolescents from medium and high SES backgrounds were significantly more likely to report very adequate cooking skills compared to those from low SES backgrounds (OR = 2.17, 95% CI: 1.20–4.13, p = 0.013; and OR = 3.57, 95% CI: 1.88–7.08, p < 0.001, respectively). Furthermore, attending a private school (with public funds) was associated with lower odds of perceiving cooking skills as very adequate compared to attending a public school (OR = 0.44, 95% CI: 0.24–0.76, p = 0.005).ConclusionsThe findings from this study suggest the importance of attending the needs of specific groups such as male adolescents, those from lower SES backgrounds and those in publicly funded private schools. In addition, our results suggest the need to question the gender norms traditionally associated to cooking. Our results can help design interventions that enhance cooking skills among adolescents. These interventions can foster healthier eating habits and ultimately reduce diet-related conditions in adolescence and later in adulthood.